2022
DOI: 10.1186/s40798-022-00431-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Plyometric Training on Lower Body Muscle Architecture, Tendon Structure, Stiffness and Physical Performance: A Systematic Review and Meta-analysis

Abstract: Background Plyometric training (PT) has been widely studied in sport science. However, there is no review that determines the impact of PT on the structural variables and mechanical properties of the lower limbs and physical performance. Objective The aim of this systematic review and meta-analysis was to determine the effects of PT on lower body muscle architecture, tendon structure, stiffness and physical performance. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 117 publications
3
23
0
1
Order By: Relevance
“…The main findings of the present meta-analysis indicated small to moderate effects of plyometric jump training on skeletal muscle hypertrophy [SMD = 0.47 (95% CIs = 0.23-0.71)], regardless of sex, age, and training experience. The current outcomes corroborate the results of a recently published systematic review with meta-analysis where authors reported a moderate effect of plyometric jump training on muscle thickness (SMD = 0.59) and fascicle length (SMD = 0.51) in healthy adults (Ramírez-delaCruz et al, 2022). However, our results are relatively more conservative, which we attribute to our more stringent inclusion criteria for plyometric jump training as well as the comparison of the plyometric jump training to an active/ passive control group.…”
Section: Main Effectsupporting
confidence: 90%
See 4 more Smart Citations
“…The main findings of the present meta-analysis indicated small to moderate effects of plyometric jump training on skeletal muscle hypertrophy [SMD = 0.47 (95% CIs = 0.23-0.71)], regardless of sex, age, and training experience. The current outcomes corroborate the results of a recently published systematic review with meta-analysis where authors reported a moderate effect of plyometric jump training on muscle thickness (SMD = 0.59) and fascicle length (SMD = 0.51) in healthy adults (Ramírez-delaCruz et al, 2022). However, our results are relatively more conservative, which we attribute to our more stringent inclusion criteria for plyometric jump training as well as the comparison of the plyometric jump training to an active/ passive control group.…”
Section: Main Effectsupporting
confidence: 90%
“…However, our results are relatively more conservative, which we attribute to our more stringent inclusion criteria for plyometric jump training as well as the comparison of the plyometric jump training to an active/ passive control group. In sum, the findings of the current study as well as those of recent ones (Grgic et al, 2020;Ramírez-delaCruz et al, 2022) question the common belief, indicating that plyometric jump training can indeed increase not only the motor drive to the active muscles but also skeletal muscle hypertrophy.…”
Section: Main Effectsupporting
confidence: 73%
See 3 more Smart Citations